2019
DOI: 10.1177/0886260519863192
|View full text |Cite
|
Sign up to set email alerts
|

Individual Resilience: A Major Protective Factor in Peer Bullying and Victimization of Elementary School Children in Israel

Abstract: Peer violence in school has become a major issue for schools around the world. The present study examined the impacts of cultural settings and of protective individual attributes on peer bullying and victimization in school. These protective attributes were self-esteem, sense of autonomy, emotional regulation, and individual resilience. Participants were 112 Jewish and 55 Arab Bedouin pupils 10 to 11 years old. It was hypothesized that Jewish pupils would score lower than Bedouin pupils on bullying and on vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 75 publications
0
17
0
1
Order By: Relevance
“…Recently, international researchers suggested that successful interventions in school bullying victimization should not only target mitigating risk factors but also promote protective/promotive factors (i.e., factor associated with a lower likelihood of school bullying victimization) (e.g., Smith, 2014;Zych et al, 2015b;Zych, Farrington, Llorent, & Ttofi, 2017;Zych, Farrington, & Ttofi, 2019b). However, until now, relatively little research has been conducted to explore the protective factors of school bullying victimization, and the majority of those studies were conducted in Western cultures or countries and concern children of older ages, such as adolescents (Cohen, Eshel, Kimhi, & Kurman, 2019;Ttofi et al, 2014;Zych et al, 2017;Zych, Farrington, & Ttofi, 2019a). In Taiwan, although the definition of school violence or bullying varied from studies to studies, findings indicated that school violence or bullying is prevalent (Chen & Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, international researchers suggested that successful interventions in school bullying victimization should not only target mitigating risk factors but also promote protective/promotive factors (i.e., factor associated with a lower likelihood of school bullying victimization) (e.g., Smith, 2014;Zych et al, 2015b;Zych, Farrington, Llorent, & Ttofi, 2017;Zych, Farrington, & Ttofi, 2019b). However, until now, relatively little research has been conducted to explore the protective factors of school bullying victimization, and the majority of those studies were conducted in Western cultures or countries and concern children of older ages, such as adolescents (Cohen, Eshel, Kimhi, & Kurman, 2019;Ttofi et al, 2014;Zych et al, 2017;Zych, Farrington, & Ttofi, 2019a). In Taiwan, although the definition of school violence or bullying varied from studies to studies, findings indicated that school violence or bullying is prevalent (Chen & Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2) The CS will be positively related to and will positively predict bullying behaviors as in a study with Estonian students between 12 and 16 years [58]. 3Resilience will be negatively related to and will negatively predict victimization as in previous studies on traditional bullying [24,25,27,28] and cyberbullying [26].…”
Section: Introductionmentioning
confidence: 93%
“…The results of Hinduja and Patchin [16], in another work performed with American students aged 12 to 17, indicated resilience as a powerful protective factor, both to prevent experiences of intimidation and to mitigate their effect, in line with the claims of other authors [8] who already suggested the possible protective nature of resilience in such situations, or as in the work of Moore and Woodcock [27], in which students with poorer resilience were more prone to engage in bullying behaviors as well as to become victims. Another study in Israel [28] analyzed the impact of cultural settings and individual protective attributes on peer bullying and victimization in school. This study, involving 112 Jewish and 55 Bedouin Arab students aged 10 to 11, considered self-esteem, a sense of autonomy, emotion regulation, and individual resilience as protective attributes, and the authors concluded that resilience could play a more important role in predicting adolescent violence in school than other personality attributes.…”
Section: Introductionmentioning
confidence: 99%
“…(Amir & Kant, 2018;Apneseth et al, 2018;Southwick et al, 2016;Woodgate, 1999). Resiliensi tidak terjadi dengan sendirinya tetapi melalui proses panjang dalam rentang kehidupan individu (Becvar, 2012;Feder et al, 2019).Banyak faktor yang mendukung perkembangan resiliensi individu diantaranya adalah penilaian positif individu,dukungan keluarga,dukungan pasangan hidup,lingkungan, budaya dan pendidikan (Cohen et al, 2019;García-León et al, 2019;Hoorelbeke et al, 2019).…”
Section: Pendahuluanunclassified